Vliv některých parametrů na kavitační vlastnosti dýzy v zařízení pro synergické spojení hydrodynamické kavitace a nízkoteplotního plazma - Petráček, Michael (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2022)
Kavitace je fyzikální jev, při kterém vlivem nízkého tlaku dochází v kapalině k tvorbě bublin páry. Ačkoliv je obecně vnímaná jako nežádoucí a je snaha ji z procesů odstranit (např. provoz turbín nebo čerpadel), ukazuje se, že v některých případech může být užitečná. Takovým případem může být její využití v čištění vody, kdy může sloužit jako důležitý článek v zefektivnění celého procesu.

Cavitation is a physical phenomenon in which low pressure causes vapour bubbles to form in a liquid. Although it is generally perceived as undesirable and efforts are made to remove it from processes (e.g. turbine or pump operation), it has been shown to be useful in some cases. One such case may be its use in water treatment, where it serves as an important link in making the process more efficient.
Influence of some parameters on cavitation properties of a nozzle in a device for synergistic connection of cavitation and low-temperature plasma
Keywords: Kavitace; Venturiho dýza; CaviPlasma; Cavitation; Venturi nozzle; CaviPlasma